Multi-potent rhizobacteria enhance banana growth and reduce chemical fertilizer input - Bright, Jeberlin Prabina; Chinnasamy, Kavitha; Maheshwari, Hemant S.; Perveen, Kahkashan; Khan, Faheema; Barasarathi, Jayanthi; Dananjeyan, Balachander; Rebouh, Nazih Y. (Frontiers in Microbiology, 2025)
IntroductionThe present investigation isolated efficient potassium-solubilizing bacteria (KSB) from the banana rhizosphere and, along with nitrogen- and phosphorus-transforming strains from TNAU, evaluated their impact on banana growth, yield, and fertilizer reduction.MethodsSolid and liquid-based formulations using the nitrogen-fixing bacterium Azospirillum brasilense Sp7 (A. b Sp7), phosphorus-solubilizing bacterium Bacillus megaterium Pb1 (B. m Pb1), and the newly isolated potassium-solubilizing bacteria Agrobacterium pusense (A. p. KRBKKM1) and Bacillus paralicheniformis (B. p KRBKKM2) were prepared and used for inoculation in the field experiment. HPLC profiling of KSBs showed that A. p. KRBKKM1 produced propionic acid, and B. p KRBKKM2 produced butyric and propionic acids.ResultsAmong the two formulations tested, the liquid formulation had a significantly greater influence on the yield and yield-attributing traits than the solid-based ones. Treatments consisted of 75% NPK chemical fertilizer + 2 mL A. b Sp7 + 2 mL B. m Pb1, along with 1 mL A. p. KRBKKMI and 1 mL B. p KRBKKM2 (T10-30.65 t ha−1), and 75% NPK + 2 mL A. b Sp7 + 2 mL B. m Pb1, along with 2 mL A. p. KRBKKMI and 2 mL B. p KRBKKM2 (T11-30.82 t ha−1) significant impacted the banana yield parameters.DiscussionPrincipal component analysis revealed that treatments T10 and T11 positively correlated with yield-related parameters. Pearson correlation analysis revealed that crop yield was positively correlated with the bunch weight (r = 1.00***), fruit weight (r = 0.84**), and number of fingers per bunch (r = 0.76**), in both the solid and liquid formulations. In conclusion, the present investigation demonstrated a 25% reduction in chemical inputs when using NPK biofertilizers and contribute to increased agricultural productivity.